Blinded by the brand: inauthentic salesperson brand attachment and its influence on customer purchase intentions. Issue 3 (3rd July 2021) - Beeler, Lisa; Zablah, Alex; Rapp, Adam
Abstract: Prior research finds that the more attached salespeople are to a brand they sell, the more effort they extend on behalf of the brand, thus improving sales performance. However, high salesperson brand attachment may also have undesirable consequences that are only evident when viewed from the customers' perspective. We argue that brand attachment can have a "blinding effect" on salespeople, leading them to adopt emotionally laden sales strategies that diminish customer brand trust and, by extension, their intent to purchase the brand. We explore these ideas using data collected from salespeople in the direct selling industry. The data collected includes 20 exploratory interviews with salesperson-customer dyads, a field study of 153 salespeople and 98 matched customers, and analyses that allow for the presence of non-linear, moderated effects. The salesperson data provide evidence of a brand attachment bright side (affirming prior research findings) while the dyadic data confirm the existence of a dark side that emerges when salespeople employ inauthentic selling strategies. The study findings point to the potential perils of internal marketing investments directed at enhancing salesperson-brand bonds.